In Estimated Good Prognosis Patients Could Unexpected "Hyporesponse" to Controlled Ovarian Stimulation be Related to Genetic Polymorphisms of FSH Receptor?. (August 2016) - Alviggi, Carlo; Conforti, Alessandro; Caprio, Francesca; Gizzo, Salvatore; Noventa, Marco; Strina, Ida; Pagano, Tiziana; De Rosa, Pasquale; Carbone, Floriana; Colacurci, Nicola; De Placido, Giuseppe
It has been reported that 10% to 15% of young normogonadotrophic women show suboptimal response to standard gonadotropin-releasing hormone—a long protocol. These patients require higher doses of exogenous follicle-stimulating hormone (FSH). This phenomenon could be associated with genetic characteristics. In this study, FSH receptor polymorphism was retrospectively evaluated in 42 normoresponder young women undergoing an in vitro fertilization/intracytoplasmic sperm injection cycle; patients were stratified according to recombinant human FSH (r-hFSH) consumption. We selected 17 normoresponder young patients who required a cumulative dose of recombinant FSH (rFSH) >2500 UI (group A). A control group was randomly selected among patients who required a cumulative dose of rFSH <2500 UI (group B). Follicle-stimulating hormone receptor (FSH-R) 307Ala and 680Ser variants were analyzed in all our patients. Our results show that the mean number of rFSH vials (36.3 ± 7.5 vs 28.6 ± 4.5, P = .0001) and days of stimulation (12.7 ± 2.4 vs 10.8 ± 2.8, P = .03) were significantly lower in group B, whereas the number of oocytes retrieved (7.1 ± 1.5 vs 9.6 ± 2.4; P = .0005) and the average number of embryos transferred (2.1 ± 0.7 vs 2.7 ± 0.4; P = .001) were significantly lower in group A. Estradiol serum levels on the human chorionic gonadotrophin day were significantly lower in group A (997.8 ± 384.9 pg/mL vs 1749.1 ± 644.4; P = .0001). The incidence of the Ser/Ser genotype was higher in patients with higher r-hFSH consumption (group A; P = .02). Based on our results, we hypothesize an association between the FSH-R polymorphisms and a "hyporesponse" to exogenous FSH.